Design and Selection of Engineered Lytic Proteins With Staphylococcus aureus Decolonizing Activity - Gutiérrez, Diana; Rodríguez-Rubio, Lorena; Ruas-Madiedo, Patricia; Fernández, Lucía; Campelo, Ana Belén; Briers, Yves; Nielsen, Martin Weiss; Pedersen, Karl; Lavigne, Rob; García, Pilar; Rodríguez, Ana (Frontiers in Microbiology, 2021)
Staphylococcus aureus causes various infections in humans and animals, the skin being the principal reservoir of this pathogen. The widespread occurrence of methicillin-resistant S. aureus (MRSA) limits the elimination and treatment of this pathogen. Phage lytic proteins have been proven as efficient antimicrobials against S. aureus. Here, a set of 12 engineered proteins based on endolysins were conceptualized to select the most optimal following a stepwise funnel approach assessing parameters including turbidity reduction, MIC, time-kill curves and antibiofilm assays, as well as testing their stability in a broad range of storage conditions (pH, temperature, ionic strength). The engineered phage lysins LysRODI∆Ami and ClyRODI-H5 showed the highest specific lytic activity (5 to 50 times higher than the rest), exhibited a shelf-life of up to six months and remained stable at temperatures of up to 50 ºC and in a pH range from 3-9. LysRODI∆Ami showed the lower MIC values against all staphylococcal strains tested. Both proteins were able to kill 6 log units of the strain S. aureus Sa9 within five minutes and could remove preformed biofilms (76 % and 65 %, respectively). Moreover, LysRODI∆Ami could prevent biofilm formation at low protein concentrations (0.15 - 0.6 µM). Due to its enhanced antibiofilm properties, LysRODI∆Ami was selected to effectively remove S. aureus contamination in both intact and disrupted keratinocyte monolayers. Notably, this protein did not demonstrate any toxicity towards human keratinocytes, even at high concentrations (22.1 µM). Finally, a pig skin ex vivo model was used to evaluate treatment of artificially contaminated pig skin using LysRODI∆Ami (16.5 µg/cm2). Following an early reduction of S. aureus, a second dose of protein completely eradicated S. aureus. Overall, our results suggest that LysRODI∆Ami is a suitable candidate as antimicrobial agent to prevent and treat staphylococcal skin infections